KARAKTERISTIK SENSORIS DAN KIMIA FLAKES DARI TEPUNG KOMPOSIT PISANG GOROHO (Musa acuminate L), UBI JALAR KUNING (Ipomea batatas L) DAN KACANG MERAH (Phaseolus vulgaris L) - Ardiyani, Niluh Putu Sri; Nurali, Erny J. N.; Lalujan, Lana E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2021)
ABSTRACTThe parameters tested were sensory properties (color, taste, smell and texture) and chemical properties (moisture content, ash, fat, protein, carbohydrate and total calories). From the results of the study it was stated that flakes made from a mixture of goroho flour, yellow sweet potato flour and red bean flour had sensory characteristics in the form of a gray to-brown color, had goroho flavored, having a sweet and crispy taste increasing with the increasing numbers of yellow sweet potato flour. In conclusion, the most preferred formula for flakes is flakes made from 60% goroho flour + 30% yellow sweet potato flour + 10% red bean flour, based on the overall organoleptic assessment results obtained an average value of 3.59 (categorized as like). Flakes made from a mixture of goroho flour, yellow sweet potato flour and red bean flour have a chemical composition with a range of moisture content values of 2.41% - 2.75%; ash 3.59% - 4.07%; fat 0.16% - 0.22%; protein 4.02% - 4.30%; carbohydrates 89.05% - 89.42% and calories 374.44 kcal - 375.74 kcal per 100 g Keywords: goroho plantain, yellow yam, red bean, flakes. ABSTRAKParameter yang diuji adalah sifat sensori (warna, rasa, bau dan tekstur) dan sifat kimia (kadar air, abu, lemak, protein, karbohidrat dan kalori total). Dari hasil penelitian disebutkan bahwa serpih yang terbuat dari campuran tepung goroho, tepung ubi jalar kuning dan tepung kacang merah memiliki ciri sensoris berupa warna abu-abu hingga kecoklatan, memiliki rasa goroho, memiliki rasa manis dan renyah. rasa semakin meningkat dengan bertambahnya jumlah tepung ubi jalar kuning. Kesimpulannya formula yang paling disukai untuk flakes adalah flakes yang terbuat dari 60% tepung goroho + 30% tepung ubi jalar kuning + 10% tepung kacang merah, berdasarkan hasil penilaian organoleptik secara keseluruhan diperoleh nilai rata-rata 3,59 (berkategori suka). Flakes yang terbuat dari campuran tepung goroho, tepung ubi jalar kuning dan tepung kacang merah memiliki komposisi kimia dengan kisaran nilai kadar air 2,41% - 2,75%; abu 3,59% - 4,07%; lemak 0,16% - 0,22%; protein 4,02% - 4,30%; karbohidrat 89,05% - 89,42% dan kalori 374,44 kkal - 375,74 kkal per 100 g.Kata kunci: pisang goroho, ubi jalar kuning, kacang merah, flakes.